Synergistic effects of Chinese herbal formula combined with Microcin J25 against Escherichia coli and Salmonella in calf diarrhea and clinical evaluation of preventive and therapeutic effects in the Ningxia region - Ding, Dong-Zhao; Zhu, Lei-Xin; Shao, Qian; Li, Xin; Tong, Yin-Chao; Zhang, Wen; Fan, Yun-Peng; Yang, Qi; Wang, Fu-Jiang; Qing, Su-Zhu; Zhang, Wei-Min (Frontiers in Veterinary Science, 2025)
IntroductionCalf diarrhea is one of the most common diseases causing significant economic losses in the livestock industry. This article aims to investigate the bacterial causes of calf diarrhea in the Ningxia region and to evaluate the synergistic antibacterial effect of Chinese Herbal Formula (CHF) and Microcin J25 (MccJ25) on pathogenic bacteria, as well as its clinical prevention and treatment effects on calf diarrhea.MethodsA total of 100 diarrheic fecal samples were collected from calves across 10 cattle farms in the Ningxia region. Bacterial isolation and identification were performed to detect E. coli and Salmonella strains. The in vitro synergistic antibacterial effects of a Chinese Herbal Formula (CHF) combined with Microcin J25 (MccJ25) were evaluated using antimicrobial susceptibility testing. Furthermore, in vivo prevention and treatment trials were conducted to assess the efficacy of the CHF-MccJ25 combination against calf diarrhea, including evaluation of clinical symptoms, fecal microbial composition, and immune parameters.ResultsThe results showed that out of 100 diarrheic calves fecal samples were collected from 10 cattle farms in the Ningxia Hui Autonomous Region. 97 E. coli strains and 20 Salmonella strains were detected. In vitro, the combination of Chinese Herbal Formula (CHF) and Microcin J25(MCJ) showed a synergistic inhibitory effect against E. coli and Salmonella. Moreover, the combined treatment also exhibited virulence-inhibitory activity. In vivo, the combination effectively reduced the incidence of diarrhea in healthy calves in a dose-dependence.DiscussionIn summary, our study indicated that the combination of Chinese Herbal Formula (CHF) and Microcin J25(MCJ) effectively combated multidrug-resistant E. coli and Salmonella, improving both prevention and treatment of calf diarrhea by enhancing immunity and restoring gut microbiota balance.